1998
DOI: 10.1136/jmg.35.10.841
|View full text |Cite
|
Sign up to set email alerts
|

Familial cylindromatosis mimicking tuberous sclerosis complex and confirmation of the cylindromatosis locus, CYLD1, in a large family.

Abstract: A large Dutch family had been known for many years to be affected with skin tumours labelled as adenoma sebaceum, which were inherited in an autosomal dominant fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…D16S770, which is non-recombinant here, is just 0.67 cM distal to D16S416, the distal recombinant marker in the other family reported by Biggs et al (1995). Verhoef et al (1998) did not report recombinant markers on 16q. Thus, the non-recombinant interval in this family is approximantly 15 cM, with no recombination that narrows the published CYLD1 6-cM interval (Biggs et al 1995).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…D16S770, which is non-recombinant here, is just 0.67 cM distal to D16S416, the distal recombinant marker in the other family reported by Biggs et al (1995). Verhoef et al (1998) did not report recombinant markers on 16q. Thus, the non-recombinant interval in this family is approximantly 15 cM, with no recombination that narrows the published CYLD1 6-cM interval (Biggs et al 1995).…”
mentioning
confidence: 72%
“…This suggested that CYLD1 is a tumor suppressor gene that follows the classic two-hit model (Knudson 1971). Verhoef et al (1998) reported a Dutch family also linked to CYLD1 and in which three tumors showed LOH at one non-recombinant marker (no further tumor analysis was performed). In addition, 16q LOH has been observed in sporadic HC tumors, suggesting that the same gene is involved in both familial and sporadic forms (Biggs et al 1996).…”
mentioning
confidence: 95%
“…Furthermore, TEs and cylindromas often coexist in patients with the tumor predisposition syndrome hereditary multiple epithelioma (MIM 132700) (37,38). TE and BCC occur in the multiple familial TE syndrome (MIM 60͞606), and trichoblastoma and BCC often develop within a congenital malformation called sebaceous nevus, in which deletions in the PTCH1 gene region were recently reported (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, two additional families have been published, both of which exhibit strong evidence of linkage to this locus (Verhoef et al 1998;Thomson et al 1999). Analysis of tumours from the original two families has shown that more than 70% exhibit loss of heterozygosity (LOH) in the vicinity of CYLD and, in all cases, the allele lost is the wild-type allele inherited from the non-mutation-carrying parent (Biggs et al 1995).…”
Section: Introductionmentioning
confidence: 97%